European Integration and the New Global Disorder. (12th February 2021) - Lavery, Scott; Schmid, Davide
Abstract: The global context within which European integration takes place is changing. The rise of China continues and the leadership of the USA has come under strain, while the global economy remains trapped in a phase of stagnation. We argue that, to capture these dynamics, EU studies would benefit from tracing the interactions between global order and contemporary dynamics within the EU. European integration has been decisively shaped by two phases of US‐led global order in the past. However, we argue that a new global disorder has emerged. The decentring of globalization, geopolitical turbulence, monetary and financial instabilities and ideological fluidity are reshaping the context within which EU integration unfolds. This presents an old European question but under a new set of volatile conditions: how to secure a degree of relative autonomy within a rapidly changing global political economy.